The Effect of Optical Element Calibration Error on the Performance of the High- precision Light Rangefinder - Petrosyan, H.; Hayrapetyan, Ye; Petrosyan, Stepan; Tsaturyan, A. (European Journal of Applied Sciences, 2026)
Observations were carried out to study the influence of calibration and alignment of individual optical elements in the electro-optical channel on the performance of an ultra-precise photometer. The amount of light in the minimum signal of the demodulation curve was determined depending on the calibration of the crystal and the analyzer in the transmitting and receiving channels. Tolerances for calibration errors of the analyzer and the crystal are presented. Acceptable alignment errors of optical elements were identified and mathematically substantiated, showing that in the modulator and demodulator these must be achieved with an accuracy of 0.5°. The relationship between crystal orientation and residual light under increased voltage applied to the crystals was also established. It was further demonstrated that when using two separate electro-optical crystals in the transmitting and receiving channels, the error magnitude is determined by the orientation errors of the crystals and the analyzer, which must not exceed 0.25°.